Monitoring the Nervous System for Anesthesiologists and Other Health Care Professionals - Koht, Antoun; Sloan, Tod B.; Toleikis, J. Richard (Springer New York : Imprint: Springer, 2012)
Written and edited by outstanding world experts, this is the first portable, single-source volume on intraoperative neurophysiological monitoring (IOM).  It is aimed at all members of the operative team - anesthesiologists, technologists, neurophysiologists, surgeons, and nurses. Now commonplace in procedures that place the nervous system at risk, such as orthopedics, neurosurgery, otologic surgery, vascular surgery, and others, effective IOM requires an unusually high degree of coordination among members of the operative team.  The purpose of the book is to help team members acquire a better understanding of one another's roles and thereby to improve the quality of care and patient safety.    •                     Concise and thorough •                     Comprehensive coverage of monitoring techniques, from deep brain stimulation to cortical mapping •                     Synoptic coverage of anesthetic management basics •                     23 case-based examples of procedures, including surgery of the aortic arch, ENT and anterior neck surgery, intracranial aneurysm clipping, and interventional neuroradiology •                     Monitoring in the ICU and of cerebral blood flow.